Kant's theory of taste a reading of the critique of aesthetic judgment - Allison, Henry E. 1937-2023 (Cambridge Univ. Press, 2001)
This book constitutes one of the most important contributions to recent Kant scholarship. In it, one of the pre-eminent interpreters of Kant, Henry Allison, offers a comprehensive, systematic, and philosophically astute account of all aspects of Kant's views on aesthetics. The first part of the book analyses Kant's conception of reflective judgment and its connections with both empirical knowledge and judgments of taste. The second and third parts treat two questions that Allison insists must be kept distinct: the normativity of pure judgments of taste, and the moral and systematic significance of taste. The fourth part considers two important topics often neglected in the study of Kant's aesthetics: his conceptions of fine art, and the sublime
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Erscheinungsjahr des E-Books: 2010
Keywords: Kant, Immanuel / 1724-1804 / Kritik der ästhetischen Urteilskraft; Kant, Immanuel -- 1724-1804; Kant, Immanuel -- 1724-1804 -- Kritik der ästhetischen Urteilskraft; Ästhetik; Aesthetics; Judgment (Aesthetics); Geschmack -- Ästhetik; Ästhetisches Urteil